Synthesis of Magnetic Halloysite Composites for the Effective Removal of Tetracycline Hydrochloride from Aqueous Solutions - Weisheng Guan; Xu Wang; Jianming Pan; Junru Lei; Ya Zhou; Chenchen Lu; Yongsheng Yan (Adsorption Science & Technology)
Herein, we explain an effective method for the synthesis of halloysite/CoFe 2 O 4 magnetic composites (magnetic halloysite nanotubes or MHNTs) and their use as as adsorbents to effectively remove tetracycline hydrochloride (TC–HCl) from aqueous solutions. The synthesized composites were characterized by the following methods: Fourier transform infrared, X-ray diffraction, transmission electron microscopy, vibrating sample magnetometry and atomic absorption spectrometry. Our study results indicated that MHNTs have strong magnetic (Ms = 34.02 emu/g) and low leakage properties. The adsorption capacities of MHNTs were investigated by performing a series of experiments with different pH, temperatures, initial concentrations and reaction time. The Langmuir isotherm model fitted to equilibrium data better than the Freundlich model. The kinetic properties of the composites were well-described by applying the pseudo-second-order equation. Even after carrying out two repeated experimental cycles, the reusability of the synthesized composites did not obviously degenerate.